Bridging the Gap Between Energy and the Environment - Flumerfelt, John (Maine Policy Review, 1993)
Energy and environmental policies have always been intertwined, but the exact nature of those interrelationships is often difficult for the non-technical reader to understand. In an analysis that was originally included in an appendix of the Report of the Maine Commission on Comprehensive Energy Planning, the former director of Maine’s Office of Energy, John Flumerfelt, provides a clear and concise graphical summary of the relation between energy use and air pollution in Maine. His presentation frames the issues in ways that identify important energy and environmental questions for the state.